2017
DOI: 10.1103/physrevb.95.085104
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of quantum critical wave functions in dissipative impurity problems

Abstract: Quantum phase transitions reflect singular changes taking place in a many-body ground state; however, computing and analyzing large-scale critical wave functions constitutes a formidable challenge. Physical insights into the sub-Ohmic spin-boson model are provided by the coherent-state expansion (CSE), which represents the wave function by a linear combination of classically displaced configurations. We find that the distribution of low-energy displacements displays an emergent symmetry in the absence of spont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…As one of successful approaches that enables direct access to the ground-state wave function, the variational method has recently been adopted to study SBM, where the form of the trial wave function plays a vital role in obtaining the ground state [29,42,46]. In this work, a systematic coherent-state expansion, termed as the "multi-D 1 ansatz", is used as the variational ansatz, which has been proved to be efficient in tackling the ground-state phase transitions and quantum dynamics of SBM and its variant [29,30,48],…”
Section: Model and Methodsmentioning
confidence: 99%
“…As one of successful approaches that enables direct access to the ground-state wave function, the variational method has recently been adopted to study SBM, where the form of the trial wave function plays a vital role in obtaining the ground state [29,42,46]. In this work, a systematic coherent-state expansion, termed as the "multi-D 1 ansatz", is used as the variational ansatz, which has been proved to be efficient in tackling the ground-state phase transitions and quantum dynamics of SBM and its variant [29,30,48],…”
Section: Model and Methodsmentioning
confidence: 99%
“…All these findings in the MCS variational study provide strong evidence of the second-order QPT in the spin-boson model with RWA. As found recently by Blunden-Codd et al [32] that a very accurate wave function can be only obtained by at least 100 coherent states, by N c = 6 coherent states the MCS results for the order parameter and energy still slightly deviate from those by VMPS above the critical points.…”
Section: Evidence For the Second-order Qpt By Mcs Variational Studiesmentioning
confidence: 59%
“…As mentioned above, most analytical predictions for the SBM are obtained deep in the scaling limit, while numerical results necessarily involve only moderately large values of . When comparing results, it is common in the literature to evaluate analytical expressions with a re-scaled coupling strength to account for this [ 45 , 46 , 47 ], which we have applied in Figure 5 . We found that a constant factor gave excellent agreement across the parameter space for both one and two-bath SBMs, as shown in the inset of Figure 5 .…”
Section: Resultsmentioning
confidence: 99%